Infertile women with a history of fertility-sparing surgery for borderline ovarian tumors: IVF outcomes and the association between IVF and tumor recurrence - Yujie Li; Weie Zhao; Panyu Chen; Weiwei Zeng; Yaqi Xu; Jintao Peng; Jingjie Li (Reproductive Biology and Endocrinology)
Abstract Background Borderline ovarian tumors (BOTs) are neoplasms of low malignant potential that predominantly affect women of reproductive age. Fertility preservation through fertility-sparing surgery is widely practiced; however, concerns remain regarding the risk of tumor recurrence and the reproductive outcomes following in vitro fertilization (IVF). This study aimed to evaluate IVF/ intracytoplasmic sperm injection (ICSI) outcomes in BOTs patients post-FSS and to assess the association between ovarian stimulation parameters and tumor recurrence. Methods In this retrospective cohort study conducted at Sixth Hospital of Sun Yat-sen University from May 2010 to May 2023, 65 women with a history of FSS for BOTs who underwent IVF/ICSI were identified. After propensity score matching, 61 BOTs patients were compared with 181 control patients without ovarian tumors. Key outcomes evaluated included ovarian stimulation parameters, live birth rates, neonatal outcomes and risk factors for tumor recurrence. Results The BOTs and control groups exhibited similar outcomes regarding the number of oocytes retrieved, the quality and number of embryos, and live birth rates from the first IVF/ICSI cycles. The cumulative live birth rate over 13 years and neonatal parameters (gestational age, birth weight, and body length) were also comparable between groups. Tumor recurrence was observed in 8.62% of BOTs patients, with no significant association identified between recurrence and ovarian stimulation parameters or peak estradiol levels. Conclusions IVF/ICSI following fertility-sparing surgery for BOTs patients yields reproductive and neonatal outcomes comparable to those in patients without BOTs and does not increase the risk of tumor recurrence. These findings support the safety and efficacy of IVF as a fertility treatment option for BOTs patients after conservative surgery. Further prospective studies with larger cohorts are warranted to validate these results and refine ovarian stimulation strategies. Clinical trial number Not applicable.